Anaerobic dechlorination of trichloroethene, tetrachloroethene and 1,2-dichloroethane by an acetogenic mixed culture in a fixed-bed reactor - 458001 Wild, Alex P.; Winkelbauer, Wolfgang; Leisinger, Thomas
53